2023
DOI: 10.1001/jamanetworkopen.2023.16174
|View full text |Cite
|
Sign up to set email alerts
|

Global, Race-Neutral Reference Equations and Pulmonary Function Test Interpretation

Abstract: ImportanceRace and ethnicity are routinely used to inform pulmonary function test (PFT) interpretation. However, there is no biological justification for such use, and it may reinforce health disparities.ObjectiveTo compare the PFT interpretations produced with race-neutral and race-specific equations.Design, Setting, and ParticipantsIn this cross-sectional study, race-neutral reference equations recently developed by the Global Lung Function Initiative (GLI) were used to interpret PFTs performed at an academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 48 publications
3
9
0
Order By: Relevance
“…In recent years, a substantive body of research has demonstrated the bias associated with use of race-specific predictive equations [ 26 , 29 , 34 , 36 ]. As such, we avoided the use of race-specific equations in all our analyses and opted to use Hankinson’s non-Hispanic White predictive equation for all races and the GLI race-neutral predictive equation in a secondary analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a substantive body of research has demonstrated the bias associated with use of race-specific predictive equations [ 26 , 29 , 34 , 36 ]. As such, we avoided the use of race-specific equations in all our analyses and opted to use Hankinson’s non-Hispanic White predictive equation for all races and the GLI race-neutral predictive equation in a secondary analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Given recent debates over the merits of race-specific predicative equations for spirometry, [ 28 , 29 , 34 36 ] in addition to Hankinson’s non-Hispanic White predictive equation of lung function, we also applied a race-neutral reference equation to explore differences in COPD prevalence and mortality. We used the Global Lung Function Initiative’s (GLI) race-neutral predictive equation for this secondary analysis [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our study is one of the first to evaluate the potential impact of the new race-neutral GLI-global equations as recommended by the ATS; 15 two studies recently reported their performances in non-African populations. 32,33 Clinical utility of PEF and FEV 1 Both PEF and FEV 1 are important in the diagnosis and monitoring of CRDs like asthma. [1][2][3]6 However, FEV 1 , being the most reproducible spirometric variable, is preferred over PEF as PEF is more likely to remain normal in the presence of severe airway obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…However, the determination of which of these is best for our population requires bench-marking their relative performances to relevant clinical end-points/outcomes for our population and relevant disease groups. 15,23,32,33 Correlates and determinants Anthro-demographic measurements like standing height, weight, age, chest circumference, sitting height, chest volume and lower-limb-length are known to correlate positively with LF in children. Similar to previous reports among children, [10][11][12]22,31,[50][51][52][53][54][55] standing height was the most correlated with our PEF and FEV 1 .…”
Section: Fit Of Fev 1 Of Nigerian Children To Gli-2012 Equationsmentioning
confidence: 99%
“…Some clinical algorithms also have been identified as racially biased. For example, pulmonary function tests traditionally included a “race correction,” which resulted in Black patients being underdiagnosed regarding the prevalence and severity of pulmonary disease [19]. These are clinically important findings.…”
mentioning
confidence: 99%